Comparison of Intravenous Oxytocin with Vaginal Prostaglandin E2 for Labor Induction in Pre-Labor Rupture of Membranes at Term - Madiha Abbasi, Erum Samreen Siddiqui, Nazia Memon, Aurooj Fatima, Nasreen Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pre-labour rupture of membrane (PROM) at term is one of the most common demonstration for labour induction. PROM is the fissure of membrane before the arrival of orderly uterine shrinkage at term gestation. About 8% of the pregnant women have influence of this condition. PROM also occur when the amniotic sac ehich surround the fetus fissure before the onset of labour leading to the risk of maternal and fetal infection. Study design: It is a randomized and controlled study conducted at Obs and Gynae Department, Civil Hospital, LUMHS, Jamshoro and Divisional Headquarters Teaching Hospital Mirpur Azad Kashmir for the duration of six months from February 2022 to July 2022. Material and Methods: The study comprised of two groups. Each group had 30 patients. The patients that were not fulfilling the inclusion criteria were excluded from the study. The average age of patients in group 1 that is oxytocin induced was 25.4±5.4 years. Patients with prostaglandin E2 induction were included in group2 with average age as 24.7±4.5 years. Group1 had 35.9±4.2 while the average value for group 2 was 36.7±5.3. Results: The induction active labor interval was 5.9±2.1 for Oxytocin induction group while for Prostaglandin E2 induction group the value was 6.3±2.2. Whereas the induction delivery was 14.3±1.9 for Oxytocin induction group and 15.1±2.1 for Prostaglandin E2 induction group. Conclusion: It is concluded that oxytocin is a better drug for labor pain induction as compared to the prostaglandin in case of Pre-labour rupture of membrane at term. To route oxytocin via an intravenous pathway leads to a shorter delivery time and reduced rate of different infections in the mother. Keywords: PROM at term, Intravenous oxytocin and vaginal prostaglandin.